2008
DOI: 10.1007/s00436-008-1087-0
|View full text |Cite
|
Sign up to set email alerts
|

Hookworms (Uncinaria lucasi) and acanthocephalans (Corynosoma spp. and Bolbosoma spp.) found in dead northern fur seals (Callorhinus ursinus) on St. Paul Island, Alaska in 2007

Abstract: Intestines of dead northern fur seals (Callorhinus ursinus) on St. Paul Island (SPI), Alaska were inspected for specific internal parasites (hookworms and acanthocephalans) in July and August, 2007. Pups (n=64) were examined for adult hookworms (Uncinaria lucasi) and four (6.25%) were infected. The number of specimens per infected pup was 1, 2, 2, or 408. Low prevalence was similar to that determined in the last investigation (2001) in dead fur seal pups on SPI by two of the present authors (Lyons and Spraker)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…Corynosoma strumosum was initially described by Rudolphi (1802) from harbor seal (Phoca vitulina Linnaeus). Th is species was also reported in various marine mammals, terrestrial carnivores and aquatic birds throughout the Arctic, Pacifi c and At- lantic Oceans, and in the Caspian Sea (Delyamure, 1955;Dailey & Brownell, 1972;Shults, 1982;Yurakhno, 1998;Nickol et al, 2002;Ionita et al, 2008;Amin et al, 2011). Morphologically, our specimens of C. strumosum are consistent with the original description of the species.…”
Section: Corynosoma Lühe 1904supporting
confidence: 87%
“…Corynosoma strumosum was initially described by Rudolphi (1802) from harbor seal (Phoca vitulina Linnaeus). Th is species was also reported in various marine mammals, terrestrial carnivores and aquatic birds throughout the Arctic, Pacifi c and At- lantic Oceans, and in the Caspian Sea (Delyamure, 1955;Dailey & Brownell, 1972;Shults, 1982;Yurakhno, 1998;Nickol et al, 2002;Ionita et al, 2008;Amin et al, 2011). Morphologically, our specimens of C. strumosum are consistent with the original description of the species.…”
Section: Corynosoma Lühe 1904supporting
confidence: 87%
“…Comparison of current fi ndings on prevalence of U. lucasi in dead NFS pups with published data from similar studies (Olsen, 1958;Lyons, 1963;Lyons et al, 2000;Ionita et al, 2008;Lyons et al, 2012) revealed decrease of hookworm prevalence during last decades (fi g. 5).…”
Section: Resultssupporting
confidence: 70%
“…Interestingly, in C. cetaceum , C. hamanni and C. pseudohamanni , the inward secondary folding that is generated by the Ds results in a complete ring (Fig. 9b; see also figure 1a in Ionita et al [19]), whilst in species with a more eccentric placement of the neck, only a posterior semi-circular fold can be formed due to space limitation for D3 and D4 (see figure 1c, d in Ionita et al [19]).…”
Section: Discussionmentioning
confidence: 99%